The petrology of the Khale dolerite sheet - Eales, Hugh V (Rhodes University, Faculty of Science, Department of Geology, 1953)
In the hills and in the plain of the Khale area are exposed two sheets of quartz-dolerite, the upper sheet being locally mushroom-shaped. The rock corresponds loosely with the Downes mountain type of dolorite, and contains numerous horizons of coarse-grained dolorite-pegmatite. The plagioclase felspars are described with special reference to the variation of grain-size, the features of zoned crystals, and the possible causes of a peculiar brown clouding in the basic zones of the crystals. Phenocrysts of augite and pigeonite, as well as plagioclase are recorded in the chilled contact rock. The micrometric data indicate that the mineral composition of the specimens is largely governed by the oxidation state of the iron, and that the Soret effect has caused the marginal rock to be enriched in basic elements. Hydrothermal veinlets composed largely of chlorite occur in both the dolorite and the country rock, and evidence suggests that veins of both residual material and mobilised granite occur in the upper finer-grained dolorite.
Keywords: Petrology -- Botswana; Diabase -- Botswana